(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2025)
The article explores the relationship between aesthetics, politics, and identity in the play Anjos de Cara Suja, created by CiA dXs TeRrOrIsTaS in collaboration with trans women and travestis who survived the prison system. The narrative follows the stories of, two trans women who faced social and institutional violence. The text examines makeup and costume design as tools of resistance and identity reconstruction, highlighting the concept of “aesthetics of precariousness” and practices such as textile transmutation. The research reveals how theatrical characterization and its creative processes can act as tools for empowerment and social transformation for marginalized communities.